How Does Temporary Agency Work Impact German Agency Workers? - Alexander Spermann (Institute for the Study of Labor (IZA), 2013)
The enormous speed of change in the working world is associated with greater job insecurity. As a dynamic external flexibilization instrument, temporary agency work is characterized by high labor turnover rates. As a result, agency workers might perceive more job insecurity than permanent staff. This paper surveys German empirical studies on outcome variables such as job satisfaction, commitment, health, employability, social participation and effects on personal life for agency workers. It is enriched by practical experience gathered at Randstad, Germanys leading staffing firm, and also provides a summary of recent research on job stability for agency workers.
Keywords: I2; J2; J4; 330; temporary agency work; staffing industry; job satisfaction; commitment; employability